Embracing the Social in Social Media : An Analysis of the Social Media Marketing Strategies of the Los Angeles Kings - Armstrong, Cole G. and Delia, Elizabeth B. and Giardina, Michael D. (Communication & Sport, 2016)
This article addresses the rise of social media in professional sport and the varying ways in which sport organizations have interacted with consumers in the social media environment. We examine one particularly interesting case: The innovative social media marketing practices of the Los Angeles Kings hockey organization, most especially through its twitter account @LAKings. Through the use of digital ethnography, we analyze and interpret official statements produced within the context of the Kings marketing and consumer strategies. We argue that the Los Angeles Kings’ social media strategy illustrates the potential collaborative efforts of an organization and its consumers in a social media space. This “coexistence” between brand and consumer provides the organization an opportunity to encourage relationship development and brand community.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTE0NTMyOTE0